Yoga practices for different blood types based on occi-dental – oriental food habits - Acharya, Balkrishna; Gowda, Paran; Bhattarai, Rachna; Bhandari, Rudra b.; Singh, Kuldeep; Verma, Anita (International Journal of Health, 2017)
Objective: The objective of this paper is to bring the relationship between blood types versus Occidental – Oriental Food Habits (OOFH) along with Yoga practices for better public health and wellness. Methodology: Sample sizes of 50 persons are selected for the study. Clinical blood type classifications and suitable diet combinations, OOFH items are worked out by trial and error method in a laboratory. A Yoga Wellness scoring card or impact card is developed to measure yoga practices.Results: The trial and error method led to innovative development of 10 basic organic food items with 50,000 variations are shown empirically for clinically tested 4 blood groups. Secondly, by using OOFH items, one can maintain a healthy body-mind. Thirdly, yoga wellness card is developed can be used as a health education and communication tool for healthy life style. Lastly, stress related issues are treated with variant juices.Conclusions: The study concludes, that a recommended OOFH diet along with Wellness card helps the individuals to maintain a disease free body-mind of clinically classified of blood types. There is a scope for further research work.